Design and analysis of multiband notched pitcher-shaped UWB antenna - Pandey G.K.; Singh H.S.; Bharti P.K.; Meshram M.K. (My University, 2025)
To mitigate the interference with coexisting wireless systems operating over 3.3–3.6 GHz, 5.15–5.825 GHz, and 7.725–8.5 GHz bands, a novel triple band notched coplanar waveguide fed pitcher-shaped planar monopole antenna is presented for ultrawideband applications. Bands notched characteristics are achieved using a novel mushroom type electromagnetic band gap structure like resonator and a split ring slot. A conceptual equivalent RLC (Resistor-Inductor-Capacitor)-resonant circuit is presented for the band notched characteristics. Furthermore, the input impedance and VSWR (voltage standing wave ratio) obtained from the equivalent circuit are validated with simulated and measured results. Performances of the antennas in both, the frequency domain and the time domain are investigated. The simulated and measured results demonstrate that the proposed antennas have wide impedance bandwidth, nearly stable radiation patterns, and suppression of gain and total radiation efficiency at notched bands. © 2015 Wiley Periodicals, Inc.